Прогнозирование уровня загрязнения воздушной среды города от действующих техногенных источников - Беляев, Николай Николаевич; Русакова, Татьяна Ивановна (Национальный горный университет, Днепр, 2018)
RU: Создание методики базируется на совместном решении уравнений конвективно-диффузионного переноса примеси для каждого загрязнителя, который непосредственно поступает от предприятия и образуется дополнительно за счет химических реакций в атмосфере. Разработанное программное обеспечение позволяет проводить ряд численных экспериментов и получать зоны загрязнения атмосферного воздуха диоксидом азота,определять районы, которые наиболее подвержены загрязнению с учетом влияния метеорологических параметров.

UK: Створення методики методика базується на спільному розв’язанні рівнянь конвективно-дифузійного переносу домішки для кожного забруднювача, який безпосередньо надходить від підприємства і утворюється додатково за рахунок хімічних реакцій в атмосфері. Розроблене програмне забезпечення дозволяє проводити ряд чисельних експериментів і отримувати зони забруднення атмосферного повітря діоксидом азоту, визначати райони, які найбільш схильні до забруднення з урахуванням впливу метеорологічних параметрів.

EN: Purpose. Development of methodology and software for determining levels and zones of atmospheric air pollution by emissions from «Interpipe Nizhnedneprovsky Pipe Plant». The methodology. The prediction of the level of atmospheric air pollution by emissions is based on the mathematical model for calculating the concentration of nitrogen dioxide, which takes into account the processes of its oxidation, the formation and evaporation of sulfuric acid in the atmosphere. The numerical method is based on the common solution of the equations of convective-diffusion transfer of pollutants that comes directly from enterprises or is formed additionally due to chemical reactions in the atmosphere. The methodology is implemented using implicit difference schemes. Findings. The developed methodology and software allow to predict the levels of atmospheric air pollution by big industrial enterprises that take into account chemical transformations of pollutants in the environment. The number of numerical experiments have been carried out to estimate the levels and zones of atmospheric air pollution in the city Dnipro by nitrogen dioxide near industrial enterprises taking into account various meteorological conditions. The originality. The dependencies of atmospheric air pollution by industrial enterprise are determined based on the common solution of impurity transfer equations. These impurities are coming from sources of pollution and transformation due to chemical reactions in the atmosphere. Practical implication. The developed prediction method and software allow to determine the concentration of pollutants in the atmosphere and to assess the level of environmental hazard of big industrial enterprises. The obtained dependencies contaminant dispersion allows to predict pollution levels of environmental objects on the territory of industrial cities and take measures to protect their air environment with time.
Прогнозування рівня забруднення повітряного середовища міста від діючих техногенних джерел
Prediction the Level of Air Pollution of the City from Active Technogenic Sources
Н. Беляев: ORCID 0000-0002-1531-7882, Т. Русакова: ORCID 0000-0001-5526-3578
Keywords: промышленное предприятие; выброс; распространение; химическое. воздействие; численная модель; промислове підприємство; викид; поширення; хімічний вплив; чисельна модель; industrial enterprise; emission; dispersion; chemical interaction; numerical model; КГВ